Establishing percentiles for blood pressure based on absolute height for children and adolescents - Marco Cossio-Bolaños; Rubén Vidal-Espinoza; Felipe Castelli Correia de Campos; José Sulla-Torres; Wilbert Cossio-Bolaños; Cynthia Lee Andruske; Camilo Urra Albornoz; Rossana Gómez Campos (BMC, 2021)
Abstract Background Evaluating blood pressure (BP) is one element for diagnosing and preventing disease in student populations. The objectives of this research were to (a) identify the range of height for measuring BP adjusted for student populations and (b) propose percentiles for evaluating BP based on height. Methods A cross-sectional study was carried out with 3,013 students. Weight, height, and diastolic (DBP) and systolic (SBP) blood pressure were evaluated. Body Mass Index (BMI) was calculated. Height ranges of 5 and 10 cm were generated. Results R2 values for height ranges of 5 cm consisted of [normotensive: DBP (R2 = 10 to 13%) and SBP (R2 = 14 to 20%), and for hypertensive: DBP (R2 = 0.07 to 15%) and for SBP (R2 = 29 to 32%)]. For height ranges of 10 cm, values included: [normotensive: DBP (R2 = 10 to 15%), and SBP (R2 = 15 to 21%) and for hypertensive: DBP (R2 = 0.07 to 16%) and SBP (R2 = 29 to 35%)]. For 5 cm height ranges, diferences occurred between both sexes for DBP (in 5 height ranges from 123 to 148 cm and 158 to 168 cm) and for the SBP (in 6 height ranges from 128 to 148 cm and from 158 to 168 cm). In the 10 cm categories, diferences appeared in DBP (from 138 to 148 cm) and in the SBP (from 158 to 168 cm). Conclusions Height is a determinant for evaluating blood pressure, and height ranges of 10 cm are more suitable for children and adolescents. The proposed percentiles based on height ranges allowed assessment of the DBP and SBP suggest their use in epidemiological and educational contexts.